3x + 27 - x (2 - 4) = -13 . 195 + 13.95
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =>3x+27-2x+8=-13*100=-1300
=>x+35=-1300
=>x=-1335
b: =>100x-5050=2750
=>100x=2750+5050=7800
=>x=78
c: =>-2x-8-64:16=198
=>-2x=210
=>x=-105
1: =-2/9(15/17+2/17)=-2/9
2: \(=\dfrac{-6}{3}+\dfrac{-21}{90}\)
=-2-7/30=-67/30
3: \(=\dfrac{3}{4}\cdot\dfrac{7}{5}+\dfrac{9}{7}\cdot\dfrac{3}{2}\)
=21/20+27/14=417/140
4: =-25/13(5/19+14/19)=-25/13
5: =-7/5-45/21=-7/5-15/7=-124/35
1: =-2/9(15/17+2/17)=-2/9
2: =−63+−2190=−63+−2190
=-2-7/30=-67/30
3: =34⋅75+97⋅32=34⋅75+97⋅32
=21/20+27/14=417/140
4: =-25/13(5/19+14/19)=-25/13
5: =-7/5-45/21=-7/5-15/7=-124/35
2: \(=\dfrac{-2}{75}+\dfrac{5}{39}=\dfrac{33}{325}\)
3: \(=\dfrac{6}{11}\left(\dfrac{4}{9}+\dfrac{5}{9}\right)=\dfrac{6}{11}\)
4: \(=\dfrac{7}{19}\left(\dfrac{5}{13}+\dfrac{8}{13}-1\right)=-2\cdot\dfrac{7}{19}=-\dfrac{14}{19}\)
5: \(=\dfrac{2}{7}\left(\dfrac{4}{23}-\dfrac{27}{23}+1\right)=0\)
6: \(=\dfrac{3}{8}\left(\dfrac{3}{7}+\dfrac{4}{7}\right)+\dfrac{11}{8}=\dfrac{3}{8}+\dfrac{11}{8}=\dfrac{14}{8}=\dfrac{7}{4}\)
a,91-5(5+x)=61
=>25+5x=91-61=30
=>5x=30-25=5
=>x=1
b,\([\left(x+34\right)-50]\)x2=56
=>(x+34)-50=56:2=28
=>x+34=28+50=78
=>x=78-34=44.
c,1045-\([2015-\left(3x-24\right)]\)=5
=>2015-(3x-24)=1045-5=1040
=>3x-24=2015-1040=975
=>3x=975+24=999
=>x=999:3=333
d,\([195-\left(3x-27\right)]\)x39=4212
=>195-(3x-27)=4212:39=108
=>3x-27=195-108=87
=>3x=87+27=117
=>x=39
e,30-3(x-2)=18
=>30-3x+6=18
=>30-3x=18-6=12
=>3x=30-12=18
=>x=18:3=6
a) \(...\Rightarrow5\left(5+x\right)=91-61=30\)
\(\Rightarrow\left(5+x\right)=30:5=6\Rightarrow x=6-5=1\)
b) \(...\Rightarrow\left(x+34\right)-50=56:2=28\)
\(\Rightarrow\left(x+34\right)=28+50=78\Rightarrow x=78-34=44\)
c) \(...\Rightarrow2015-\left(3x-24\right)=1045-5=1040\)
\(\Rightarrow\left(3x-24\right)=2015-1040=975\)
\(\Rightarrow3x=975+24=999\Rightarrow x=999:3=333\)
d) \(...\Rightarrow195-\left(3x-27\right)=4212:39=108\)
\(\Rightarrow\left(3x-27\right)=195-108=87\)
\(\Rightarrow3x=87+27=114\Rightarrow x=114:3=38\)
e) \(...\Rightarrow3\left(x-2\right)=30-18=12\Rightarrow x-2=12:3=4\)
\(\Rightarrow x=4+2=6\)
\(a,91-5.\left(5+x\right)=61\\ \Rightarrow=5.\left(5+x\right)=30\\ \Rightarrow5+x=6\\ \Rightarrow x=1.\\ b,\left[195-\left(3x-27\right)\right].39=4212\\ \Rightarrow195-\left(3x-27\right)=108\\ \Rightarrow3x-27=87\\ \Rightarrow3x=114\\ \Rightarrow x=38.\)
\(91-5.\left(5+x\right)=61\)
\(\Rightarrow5.\left(5+x\right)=91-61\)
\(\Rightarrow5.\left(5+x\right)=30\)
\(\Rightarrow5+x=\dfrac{30}{5}=6\)
\(\Rightarrow x=6-5=1\)
\(\left[195-\left(3x-27\right)\right].39=4212\)
\(\Rightarrow195-3x+27=\dfrac{4212}{39}=108\)
\(\Rightarrow222-3x=108\)
\(\Rightarrow3x=222-108=114\)
\(\Rightarrow x=\dfrac{114}{3}=38\)
c)(x+4)\(^2\)-64=0
=>(x+4)\(^2\)=64
=>(x+4)\(^2\)=8\(^2\)
=>x+4=8
=>x=4
d)(x+13)\(^3\)+27=0
(x+13)\(^3\)=-27
(x+13)\(^3\)=(-3)\(^3\)
=>x+13=-3=>x=-1613.95*56+13.95*104-13.95*60=13.95*(56+104-60)=13.95*100=1395
\(a.\left[\left(x+34\right)-50\right].2=56\\ \Leftrightarrow\left(x+34\right)-50=28\\ \Leftrightarrow x+34=78\\ \Rightarrow x=44\)
\(b.1045-\left[215-\left(3x-24\right)\right]=5\\ \Leftrightarrow215-\left(3x-24\right)=1040\\ \Leftrightarrow3x-24=-825\\ \Leftrightarrow3x=-801\\ \Rightarrow x=-267\)
\(c.\left[195-\left(15x-27\right)\right].39=4212\\ \Leftrightarrow195-\left(15x-27\right)=108\\ \Leftrightarrow15x-27=87\\ \Leftrightarrow15x=114\\ \Rightarrow x=7,6\)
a) [(x+34)] - 50] . 2 = 56
=x+34-50=56:2
=> x+34-50=28
->x=28+50-34
-> x=44
b,1045 - [ 215 - ( 3x - 24 )] = 5
1045-(215-3x+24)=5
1045-215+3x-24=5
1045-215-24-5=-3x
-> 801=-3x-> x=801:(-3)=-267
,c) [ 195 - ( 15x - 27)] . 39 = 4212
(195-15x+27).39=4212
(195-15x+27)=4212/39=108
195+27-108=15x
114=15x-> x=114/15=7,6
-
\(\left[195-\left(3x-27\right)\right]\cdot39=4212\)
\(\Rightarrow\left(195-3x+27\right)\cdot39=4212\)
\(\Rightarrow\left(-3x+222\right)\cdot39=4212\)
\(\Rightarrow-3x+222=\dfrac{4212}{39}\)
\(\Rightarrow-3x+222=108\)
\(\Rightarrow3x=222-108\)
\(\Rightarrow3x=114\)
\(\Rightarrow x=\dfrac{114}{3}\)
\(\Rightarrow x=38\)
=>[195-(3x-27)]=4212:39=108
=>3x-27=195-108=87
=>3x=27+87=114
=>x=38
3x + 27 + 2x = 27150
5x = 27123
x = 27123 : 5
Vậy x = 5424,6